Increased Fas and Bcl-2 Expression on Peripheral Blood T and B Lymphocytes from Juvenile-Onset Systemic Lupus Erythematosus, but not from Juvenile Rheumatoid Arthritis and Juvenile Dermatomyositis. Issue 2 (2006) - Liphaus, Bernadete L.; Kiss, Maria H. B.; Carrasco, Solange; Goldenstein-Schainberg, Claudia
Abstract : Defective regulation of apoptosis may play a role in the development of autoimmune diseases. Fas and Bcl-2 proteins are involved in the control of apoptosis. The aims of this study were to determine the expression of Fas antigen and Bcl-2 protein on peripheral blood T and B lymphocytes from patients with juvenile-onset systemic lupus erythematosus (JSLE), juvenile rheumatoid arthritis (JRA) and juvenile dermatomyositis (JDM). Thirty-eight patients with JSLE, 19 patients with JRA, 10 patients with JDM and 25 healthy controls entered the study. Freshly isolated peripheral blood mononuclear cells (PBMC) were stained for lymphocyte markers CD3, CD4, CD8, CD19 and for Fas and Bcl-2 molecules. Expressions were measured by three-color flow cytometry. Statistical analysis was performed using Kruskal–Wallis test. Percentages of freshly isolated T lymphocytes positively stained for Fas protein from JSLE patients were significantly increased compared to healthy controls, patients with JRA and patients with JDM. Percentages of B lymphocytes positive for Fas from JSLE patients were higher than healthy controls and JRA patients. In addition, Fas expression on T cells from patients with JRA was increased compared to JDM patients. Otherwise, Fas expression on T and B cells from JRA and JDM patients were similar to healthy controls. MFI of Bcl-2 positive T lymphocytes from JSLE patients were significantly increased compared to healthy controls and JRA patients. MFI of Bcl-2 protein on B lymphocytes from JSLE patients was similar to healthy controls and patients with JRA and JDM. Bcl-2 expression did not differ between JRA and JDM patients and healthy controls. In conclusion, increased expression of Fas and Bcl-2 proteins observed in circulating T and B lymphocytes from patients with JSLE, but not from patients with JRA and JDM, suggests that abnormalities of apoptosis may be related to the pathogenesis of JSLE and probably are not a result of chronic inflammation.